2008
DOI: 10.1155/2008/715153
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Liposarcoma to the Parotid

Abstract: Distant metastases of the parotid gland are uncommon. They arise from primary tumors located in the head and neck, mainly melanoma and epidermoid carcinoma. Other histological types of metastasis are very rare. We report an exceptional case of parotid metastasis of myxoid liposarcoma in a 42-year-old man and insist on the worse prognosis of this entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
3
9
0
Order By: Relevance
“…However, the parotid gland was the third most common site for liposarcoma of the oral and salivary gland region in the AFIP series of 18 patients reported by Fanburg-Smith et al [45] Histological subtypes of the four patients included in this latter study were well differentiated/lipoma-like (2), myxoid (1) and dedifferentiated (1) liposarcoma [45]. Rare cases of liposarcoma metastatic to the parotid gland have been reported and should be included in the differential diagnosis of liposarcoma at this unusual location [46]. Bilateral atypical lipomatous tumors of the neck may coexist with bilateral lipomatous changes of the parotid in patients with Madelung disease [21].…”
Section: Rare Lipoma Variantsmentioning
confidence: 73%
“…However, the parotid gland was the third most common site for liposarcoma of the oral and salivary gland region in the AFIP series of 18 patients reported by Fanburg-Smith et al [45] Histological subtypes of the four patients included in this latter study were well differentiated/lipoma-like (2), myxoid (1) and dedifferentiated (1) liposarcoma [45]. Rare cases of liposarcoma metastatic to the parotid gland have been reported and should be included in the differential diagnosis of liposarcoma at this unusual location [46]. Bilateral atypical lipomatous tumors of the neck may coexist with bilateral lipomatous changes of the parotid in patients with Madelung disease [21].…”
Section: Rare Lipoma Variantsmentioning
confidence: 73%
“…Amel Trabelsi et al 13 and Alemán López et al 14 reported two similar cases of liposcarcomas metastatic to the parotid gland in two patients with a history of resected lower limb liposarcoma. Our case represents the third case reported in the literature of a lower extremity myxoid liposarcoma metastatic to the parotid gland.…”
Section: 3mentioning
confidence: 98%
“…Management is typically surgical excision, with or without radiotherapy. [2][3][4]13 However, these seem to be palliative measures since the prognosis is poor, and the patient is likely to die from their disease. Immunohistochemical staining with S100, which shows diffuse staining in the majority of myxoid liposarcomas, 2 was negative in our case; therefore, molecular testing played a key role in confirming the diagnosis.…”
Section: 3mentioning
confidence: 99%
“…Among the histologic subtypes most commonly encountered are renal cell carcinoma 6 , breast cancer 7 , lung cancer 8 , and prostate cancer 9 . Rarely reported entities include adrenal neuroblastoma, rhabdomyosarcoma, leiomyosarcoma, hepatocellular carcinoma, liposarcoma, and urachus adenocarcinoma of the urinary bladder [10][11][12][13] .Immunohistochemistry has improved the differential diagnosis of such lesions. Germ cell tumours in the testis usually metastasize to retroperitoneal lymph nodes, lungs, liver, and brain.…”
mentioning
confidence: 99%
“…Among the histologic subtypes most commonly encountered are renal cell carcinoma 6 , breast cancer 7 , lung cancer 8 , and prostate cancer 9 . Rarely reported entities include adrenal neuroblastoma, rhabdomyosarcoma, leiomyosarcoma, hepatocellular carcinoma, liposarcoma, and urachus adenocarcinoma of the urinary bladder [10][11][12][13] .…”
mentioning
confidence: 99%